Robustness and reproducibility of simple and complex synthetic logic circuit designs using a DBTL loop. Issue 1 (28th March 2023) - Cummins, Breschine; Vrana, Justin; Moseley, Robert C; Eramian, Hamed; Deckard, Anastasia; Fontanarrosa, Pedro; Bryce, Daniel; Weston, Mark; Zheng, George; Nowak, Joshua; Motta, Francis C; Eslami, Mohammed; et al.
Abstract: Computational tools addressing various components of design–build–test–learn (DBTL) loops for the construction of synthetic genetic networks exist but do not generally cover the entire DBTL loop. This manuscript introduces an end-to-end sequence of tools that together form a DBTL loop called Design Assemble Round Trip (DART). DART provides rational selection and refinement of genetic parts to construct and test a circuit. Computational support for experimental process, metadata management, standardized data collection and reproducible data analysis is provided via the previously published Round Trip (RT) test–learn loop. The primary focus of this work is on the Design Assemble (DA) part of the tool chain, which improves on previous techniques by screening up to thousands of network topologies for robust performance using a novel robustness score derived from dynamical behavior based on circuit topology only. In addition, novel experimental support software is introduced for the assembly of genetic circuits. A complete design-through-analysis sequence is presented using several OR and NOR circuit designs, with and without structural redundancy, that are implemented in budding yeast. The execution of DART tested the predictions of the design tools, specifically with regard to robust and reproducible performance under different experimental conditions. The data analysis depended on a novel application of machine learning techniques to segment bimodal flow cytometry distributions. Evidence is presented that, in some cases, a more complex build may impart more robustness and reproducibility across experimental conditions. Graphical Abstract